Falling in love in absentia: Grimalte and Gradissa’s mimetic desire in Juan de Flores’ Grimalte y Gradissa - Luis Fernando López (Medievalia, 2017)
Juan de Flores’ Grimalte y Gradissa is a story in which the dramatic tension is sustained by desire and by the active drive to bring that desire into fruition. Flores readapts Boccaccio’s protagonists, introducing them into his own diegetic world to attempt an intertextual reconciliation. As the drama unfolds, Fiometa’s desire for Pánfilo and Pánfilo’s “desire” for Fiometa are mimicked by Flores’ eponymous characters. Gradissa sends Grimalte to attempt their reunion. Like Gradissa had fallen in love with Pánfilo in absentia, Grimalte falls for Fiometa. This study argues that Gradissa sends her courtier to Italy because she is secretly in love with Pánfilo. Grimalte accepts her command in order to earn Gradissa’s favor. In the process Grimalte falls in love with Fiometa.